The Consumer Option Model for Withdrawal Rights in the EU: Analysis of an Alternative Design - Ranftl, Simone; Lurger, Brigitta; Brohmer, Hilmar; Athenstaedt, Ursula (American Journal of Trade and Policy, 2022)
Under EU law, consumers have a mandatory “right of withdrawal” in certain situations. Economic and legal literature raises severe doubts as to its effectiveness and fairness. In this article, an alternative design is discussed and examined within the framework of an experimental study: the “consumer option model,” in which every online consumer can choose between a purchase with and a purchase without a withdrawal right for a slightly lower price. Three study participants purchased two different products in a simulated online shop where the right of withdrawal was presented in three different frames (opt-out, opt-in, no default). The results revealed that a considerable number of participants were ready to shop without a right of withdrawal; in their choices framing and product value was of the essence, but not income, and a considerable number of participants reported an under-use of the right of withdrawal in every-day life.